(untitled) (Chemical Engineering Research Bulletin, 2016)
Fruit ripening is a natural process in which a fruit goes through various physical and chemical changes and gradually becomes sweet, coloured, soft and palatable. However, this natural process can also be stimulated by using artificial fruit ripening agents. Farmers and vendors often use artificial ripening agents to control fruit ripening rate. However, because of the potential health hazard related to the ripening agents, artificial fruit ripening process is highly debateable throughout the world. There are existing laws and guidelines to control artificial fruit ripening process. This article deals with the legal aspects of artificial fruit ripening and fruit adulteration in Bangladesh. Different laws and acts to control and prohibit fruit ripening and adulteration using hazardous chemicals are discussed in detailed here. Laws from different developed and developing countries are also listed and discussed here. Furthermore, the technical and economic issues related to the artificial fruit ripening are addressed in this study. This article aims to develop awareness among different stakeholders since it will take the active participation of the government agencies, policymakers, farmers, vendors and scientists to address different aspects of artificial fruit ripening issues and to provide an effective solution. Chemical Engineering Research Bulletin 18(2015) 30-37